2023
DOI: 10.1101/2023.03.17.533246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of meiotic entry by dual inhibition of a key mitotic transcription factor

Abstract: The mitosis to meiosis transition requires dynamic changes in gene expression, but whether and how the mitotic transcriptional machinery is regulated during this transition is unknown. In budding yeast, SBF and MBF transcription factors initiate the mitotic gene expression program. Here, we report two mechanisms that work together to restrict SBF activity during meiotic entry: repression of the SBF-specific Swi4 subunit through LUTI-based regulation and inhibition of SBF by Whi5, a homolog of the Rb tumor supp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Case studies have revealed that diverse gene targets are subject to LUTI-based repression, including the genes encoding the kinetochore subunit Ndc80 (J. Chen et al, 2017;Chia et al, 2017), the superoxide dismutase enzyme Sod1 (Vander Wende et al, 2023), the transcription factor Swi4 (Su et al, 2023), and the purine hydrolase enzyme Hnt1 (Van Dalfsen et al, 2018;Tatip et al, 2020). Importantly, the observation that the human protooncogene MDM2 is subject to LUTI-based interference has revealed this form of gene repression is broadly conserved (Hollerer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Case studies have revealed that diverse gene targets are subject to LUTI-based repression, including the genes encoding the kinetochore subunit Ndc80 (J. Chen et al, 2017;Chia et al, 2017), the superoxide dismutase enzyme Sod1 (Vander Wende et al, 2023), the transcription factor Swi4 (Su et al, 2023), and the purine hydrolase enzyme Hnt1 (Van Dalfsen et al, 2018;Tatip et al, 2020). Importantly, the observation that the human protooncogene MDM2 is subject to LUTI-based interference has revealed this form of gene repression is broadly conserved (Hollerer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%